Social benefits and costs of interventions in coconut based homesteads of central Kerala - Helen, S.; Ahamed, P. (Journal of Plantation Crops, 2011)
A research project on ’possible diversifications and restructuring of coconut based homesteads’ was implemented in six agro-ecosystems of Central Zone of Kerala covering three districts namely Palakkad, Thrissur and Eranakulam from the year 2005 to 2008 in a holistic approach with the participation of all the stakeholders. The interventions were selected by the farmers on participatory basis. Analysis of social and monitory benefits consequent to the adoption of interventions showed that all the six dimensions of Social Cost Index Value were found as the lowest in High Elevation-Medium Rainfall situation. Among all the dimensions, exploitation by middlemen was rated as the maximum Social Cost Index Value in almost all the situations and, therefore this dimension requires the attention of policy makers to ensure suitable price for the farm produce. Among the six dimensions in the Social Benefit Index Value, family labour utilisation and self confidence contributed maximum to this attribute. Benefit Index Value. It indicated that, the interventions made in the homesteads fully utilized family labour and enhanced the self confidence of the participating farmers. Social Benefit Cost Ratio was computed as the highest with 2.04 at High Elevation-Medium Rainfall situation and the lowest with 1.07 at Medium Elevation-Low Rainfall situation after three years of adoption of interventions. The interventions on restructuring of coconut based homesteads were found to be economically viable and socially desirable.